PWE-074 Hospitality discharge for alcohol related problems in north of italy: a sixteen – years period. (8th June 2018) - Rosa-Rizzotto, Erik; Caroli, Diego; Saia, Mario; Scribano, Laura; Peraro, Laura; Vicario, Serena; Lobello, Salvatore; Lazzari, Franca De
Abstract : Background and aims: WHO (2014) estimates a remarkable decline in per capita pure alcohol consumption in Italy, dropped from 18.1 to 7.1 lt in the period 1970–2013. Despite this, Italian Report on Alcohol 2016 showed an increase in drinking outside meals and a rise in consumption and binge drinking among young people (18–24, 14–17), particularly in males. The impact of these drinking styles on hospitalisation is still under-researched. This study aims to evaluate the trends of hospitality discharge for alcohol-related liver disease in the period 2000–2016 in Veneto Region in North Eastern Italy (4.8 million inhabitants). Method: Retrospective cohort analysis based on Veneto Region anonymous computerised database of hospital discharges between 2000 and 2016. All Veneto residents discharge records with principal diagnosis of alcohol-related liver disease (cod. ICD9-CM: 571.0, 571.1, 571.2, 571.3) were included in the study. The principal diagnosis was chosen as it is considered the primary reason for hospital admission. Standardised Hospitalisation Ratio (SHR) per five-year age group (ref. pop. Veneto 2008) was calculated and expressed per 100.000 population. Results: Over the period 2000–2016, 28.968 hospital admissions for alcohol-related diseases were recorded. Most part of subjects were males (74%) with a SHR more than double compared to females (53.3 vs. 18; OR:2.96; CI 95%:2.89–3.04 p<0, 05). The longitudinal analysis of the hospitalisation trend shows a 7% increase on average age in both sexes (from 58.8±9, 2 to 62.6±9, 6) and a substantial decrease of 66% in SHR (X2 trend: 3933, 326). In the last year of observation SHR tends to 19.5, and the greater risk for males is confirmed (30.2 vs. 8.8; OR:3.51; CI 95%:3.05–4.10; p<0.05). Considering the age groups, the highest decline in SHR can be found in the ranges 45–64 (from 69.2 to 34.1) and >65 (from 69.3 to 26.8). Interestingly, SHR shows a slightly rising trend in the group 25–44 betweeen 2013 and 2016 (p<0.05). Conclusion: In Veneto Region, the reduction in alcohol intake over the last 30 years has lead to a marked decrease in hospitalisation for alcohol-related diseases. However, the changes in drinking styles occurred in the age range 25–44 may explain the upward SHR trend between 2013 and 2016. Thus, in the next few years it is likely to expect an increase in hospitalisation in this age group. Public Health strategies are needed to address the new styles of alcohol consumption, especially in young people.